Fabrication of Nanodevices Through Block Copolymer Self-Assembly - Hu, Xiao-Hua; Xiong, Shisheng (Frontiers in Nanotechnology, 2022)
Block copolymer (BCP) self-assembly, as a novel bottom-up patterning technique, has received increasing attention in the manufacture of nanodevices because of its significant advantages of high resolution, high throughput, low cost, and simple processing. BCP self-assembly provides a very powerful approach to construct diverse nanoscale templates and patterns that meet large-scale manufacturing practices. For the past 20 years, the self-assembly of BCPs has been extensively employed to produce a range of nanodevices, such as nonvolatile memory, bit patterned media (BPM), fin field-effect transistors (FinFETs), photonic nanodevices, solar cells, biological and chemical sensors, and ultrafiltration membranes, providing a variety of configurations for high-density integration and cost-efficient manufacturing. In this review, we summarize recent progress in the fabrication of nanodevices using the templates of BCP self-assembly, and present current challenges and future opportunities.